PENGEMBANGAN ALAT PENANAMAN BENIH JAGUNG DAN PEMUPUKAN DALAM SATU UNIT - Muhammad Asshiddiq, Ansar; Ansar, Ansar; Nanaluih De Side, Gagassage (Jurnal Agritechno, 2025)
In an effort to achieve optimal agricultural productivity, efficiency in each stage of cultivation is a determining factor. One important stage is seed planting and fertilization, which are traditionally still carried out separately. This study aims to develop a seed planting and fertilization tool that is integrated in one unit, as an effort to improve the efficiency, effectiveness, and sustainability of the planting and fertilization process on agricultural land. This tool is designed with an integrated engineering approach, which allows seed planting and fertilizer application to be carried out simultaneously in one operation. The study was conducted with a series of systematic stages, starting from a literature study to identify needs and challenges in conventional agricultural practices. Furthermore, the concept design of the tool was carried out followed by the creation of a physical prototype made of strong and durable materials. Prototype performance testing was carried out on experimental land with various types of soil and environmental conditions to measure time and energy efficiency, accuracy of seed and fertilizer placement, and plant growth results. The results of the study showed that the developed tool was able to significantly increase time and energy efficiency compared to conventional planting and fertilization methods. In addition, this tool provides more uniform results in seed and fertilizer placement, which has a positive impact on plant growth and yields. The implication of this research is the creation of agricultural technology innovations that can support sustainable agricultural practices, reduce dependence on manual labor, and increase farmer productivity. This tool has the potential to be a solution to modern agricultural challenges, especially in efforts to achieve food security and environmental sustainability.